(untitled) (Altre Modernità, 2022)
As it has been reported for other countries, Peru has also been a territory with a high percentage of deaths due to the coronavirus pandemic. The ravages of the disease have also affected various sectors of the local population, such as the economy, education, and health. However, one of the most powerful resources to confront this pandemic has been the promotion of publicity campaigns around vaccination against COVID-19 throughout the region. In this context, the Peruvian press has displayed a series of speeches that publicize immunization through a set of benefits offered by various companies (restaurants, shopping malls, mobile phone operators, etc.). These advertising campaigns, however, erase existing power relations and social gaps. Through the critical analysis of these media discourses, this paper proposes how the Peruvian press highlights a certain class of wealthy social actors but hides other social actors who have interrupted their studies, who have suffered economic losses, who have been excluded from any economic reactivation, among other aspects. In this scenario, the analysis shows who these ‘Others’ are, and, later, how they appear discursively in this context of health crisis.